Game-Based Learning, Gamification in Education and Serious Games (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this book is to present and discuss new advances in serious games to show how they could enhance the effectiveness and outreach of education, advertising, social awareness, health, policies, etc. We present their use in structured learning activities, not only with a focus on game-based learning, but also on the use of game elements and game design techniques to gamify the learning process. The published contributions really demonstrate the wide scope of application of game-based approaches in terms of purpose, target groups, technologies and domains and one aspect they have in common is that they provide evidence of how effective serious games, game-based learning and gamification can be.